Surface thermal fronts in the Southern Atlantic and its seasonal variability obtained on the basis of satellite data - Ju. Artamonov; N. Bulgakov; P. Lomakin; E. Skripaleva; A. Artamonov; S. Stanichny (Ukrainian Antarctic Journal, 2004)
The main features of seasonal variability of the large-scale sea surface thermal fronts in the Southern Atlantic have been investigated using the SST satellite data. The comparative analysis of the specific features of the front manifestations in the western and central regions in the meridional sections along 65°, 50°, 40°, 30° and 10°W were carried out. It was shown that the fronts intensity decreases from west to east. In seasonal cycle of the fronts variability the annual harmonics predominated. The semi-annual harmonics are found near the South America and in the eastern part of the investigated region.